Analysis of Local Government Financial Statements as A Basis for Making National Economic Recovery Loan (PEN) Policies in the Jakarta Provincial Government - Nukman, Precillia; Nugroho, Bernadus Yuliarto (Journal of Management and Administration Provision, 2024)
This research was conducted to analyze local government financial statements as a basis for making decisions or policies on the use of Regional PEN Loans in the DKI Jakarta Provincial Government. Due to a decrease in revenue as a result of the covid-19 pandemic, the DKI Jakarta Provincial Government is looking for other sources of funding to finance development to meet public services. The data used include budget and realization of regional income and expenditure, as well as the value of Construction in Progress which is supported by qualitative information in Notes to Financial Statement. The research method uses descriptive qualitative by collecting data in the form of images, numbers, tables, and sentences, in the form of secondary data. The results ofthe study concluded that the information presented in the financial statements has an important role in assisting the policy making of the DKI Jakarta Provincial Government in applying for Regional PEN Loans and meeting the criteria as a loan recipient.